Mindfulness and Marital Adjustment: Experiential Avoidance, Valued Living, and Mindfulness in Marriage as Multiple Mediators - Gungor, Selen; Erus, Seher Merve; Satici, Seydi Ahmet (SAGE PUBLICATIONS INC, 2026)
The level of marital adjustment of married individuals, which is an important value area, is considered important both individually and socially. Acceptance and commitment therapy approach is increasingly applied in marital relationships. The importance of examining the relationships between mindfulness, valued living, and experiential avoidance and marital adjustment has become evident over the years. This study was conducted to examine the multiple sequential mediation of experiential avoidance, valued living, and mindfulness in marriage between married individuals' mindfulness and marital adjustment. The data were collected from a total of 430 married individuals, 257 women and 173 men, between the ages of 22 and 68. Bootstrapping procedure indicated that experiential avoidance, valued living, and mindfulness in marriage had a sequential mediating effect between mindfulness and marital adjustment. Researchers may need to pay more attention to acceptance and valued living as important factors in the relationship between mindfulness and marital adjustment.
Keywords: marital adjustment; mindfulness; mindfulness in marriage; experiential avoidance; valued living; FUNCTIONAL DIMENSIONAL APPROACH; ACTION QUESTIONNAIRE-II; COMMITMENT THERAPY; PSYCHOLOGICAL FLEXIBILITY; ACCEPTANCE; RELIABILITY; Family Studies